The Influence of University Business Incubators on their Associated University Startups - Timo VISESTAMKUL; Giuseppe STRINA (Communications of International Proceedings, 2023)
In recent years, academic entrepreneurship has become a popular topic among universities aiming to promote innovation and entrepreneurship among their students and faculty. University business incubators have been established to support the growth and development of startups founded by university members. However, much of the research on the impact of university business incubators on their associated startups has focused on spinoff startups, which are based on previous research projects or patents. This paper argues that a new category of university startups has emerged, primarily focusing on less research-based ideas, but with solid business models. Despite the growing importance of this new category of startups in the university entrepreneurship ecosystem, it has not received much attention from researchers. To investigate the impact of university business incubators on this new category of startups, a qualitative study was conducted with 5 university startups from North-Rhine-Westphalia in Germany. The study aimed to determine the perceived effectiveness of the university business incubator programs from the perspective of the university startups. Overall, this paper concludes that university business incubators play an important role in supporting the growth and development of university startups, including both spinoff startups and the emerging category of less research-based university startups. However, further research is needed to better understand the needs and challenges of this new category of startups and to develop more effective support programs for their growth and success.
Keywords: Entrepreneurship ecosystem; university business incubator; university startup.